From Text on Paper to Digital Poetry: Creativity and Digital Literary Reading Practices in Initial Teacher Education - Selfa Sastre, Moisés; Falguera Garcia, Enric (Frontiers in Psychology, 2022)
The new contexts of literary education allow for the creation of digital reading and writing practices related to what specialised literature calls digital literature. Among these practices and with an eminently theoretical content and with an examples of this content, in this paper we want to focus our gaze on cyberpoetry, conceived as an exercise in literary creativity that firstly involves use of technology and specific software for the digital creation of poetic texts and, last but not least, knowledge and mastery of poetic language and the literary conventions linked thereto. From this point of view, in initial teacher training, we work with future teachers to create cyberpoems with a dual purpose: on the one hand, to reflect on what literary reading in digital format entails and to rehearse reading mediation processes that can be carried out with this type of literature, and, on the other, to begin in the digital creation of cyberpoems that, later, may be presented and worked in a real context of the school classroom. The conclusions of all this allow us to affirm that the creation of cyberpoems is an exercise in literary creativity that has to take into account the digital dimension of the literary text and its reading comprehension in a multimodal environment.